A SENSITIVE AREA IN COMMUNICATION STUDIES: COUNTRY BRAND - Tuğçe Boran (Erciyes University, 2015)
The concepts of brand and branding have been an important agenda item of the organizations in recent years. Country brand has also gained importance following the export of commercial products and the increase in the revenue based on tourism. There are ongoing controversies over country brand concept. It has been found that there are a few studies on this issue in Turkish literature. Moreover, as having a political dimension, the topic of country and city brands is wide enough to work on.  Country brands cannot be managed as easily as trademarks, for there are many decision- makers, the area which the brand spans and people who are affected by brand management consist of different groups, there are historical prejudices and background and target people are varied.  Thus, ‘country brand’ can be considered as a ‘sensitive area’. It is substantially aimed at detecting the dimensions which constitute country brand. In this context, this paper is regarded as exploratory research. This paper focuses on explaining the concept of country brand and dimensions of it. After scanning the literature in question, a research including the opinions of university students in Turkey on country brand will be done.